2010
DOI: 10.1177/0731684410375639
|View full text |Cite
|
Sign up to set email alerts
|

Impact behavior of short and continuous fiber-reinforced polyester composites

Abstract: In this study, the impact strengths of E-glass, coir, oil palm as well as E-glass/coir and E-glass/oil palm hybrid polyester composites were studied. All types of composites were reinforced with fiber volume fractions of 30%, 40%, and 50% and fiber lengths 3, 7, and 10 mm. Composite laminates reinforced with longitudinal and transverse coir fiber mats were also studied. The number of fiber mats varied from 1, 2, 3, and 4 layers for non-spaced fiber mats and 2, 3, and 4 layers for 1.5 mm spaced fiber mats. Besi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…Wong et al investigated the impact behavior of short and continuous fiber reinforced polyester composites. The impact strengths of E‐glass, coir, oil palm as well as E‐glass/coir and E‐glass/oil palm hybrid polyester composites were noted.…”
Section: Coir Fiber‐reinforced Composites and Their Propertiesmentioning
confidence: 99%
“…Wong et al investigated the impact behavior of short and continuous fiber reinforced polyester composites. The impact strengths of E‐glass, coir, oil palm as well as E‐glass/coir and E‐glass/oil palm hybrid polyester composites were noted.…”
Section: Coir Fiber‐reinforced Composites and Their Propertiesmentioning
confidence: 99%
“…They reported a significant improvement in tensile, flexural, and compressive strengths after NaOH treatments of coir fibers. Likewise, Wong et al reported an improvement in impact strength upon reinforcement with CF in E‐glass/coir/polyester hybrid composites, due the ability of CF to dissipate impact energy. Also, an improvement in properties was reported by Asim et al for PALF/kenaf/phenolic resin hybrid composites upon addition of fibers.…”
Section: Introductionmentioning
confidence: 96%
“…The impact damage can be detected by thermally deplying method and non‐destructive test including C‐scan and X‐ray . Wong et al . investigated the impact strengths of short and continuous fiber‐reinforced polyester composites with different kinds of fiber volume fraction and fiber lengths through the experimental tests.…”
Section: Introductionmentioning
confidence: 99%